Role of bradykinin receptor B2 in mechanoreflex activation in a rat model of simulated peripheral artery disease - Williams, Auni C. (Kansas State University, 2021)
The exercise pressor reflex, and the mechanical component of the exercise pressor reflex specifically (i.e., the mechanoreflex), is exaggerated in patients with peripheral artery disease (PAD) and in a rat model of simulated PAD in which a femoral artery is ligated ~24-72 hours before the experiment. In the rat, the mechanisms and outcomes of mechanoreflex activation may be investigated by rhythmically stretching the hindlimb skeletal muscles to mimic the pattern of mechanical stimulation present during locomotion. The purpose of the present study was to investigate the role played by bradykinin B2 receptors (B2-Rs) on the sensory endings of thin fiber muscle afferents in the chronic sensitization of the mechanoreflex in the rat ligated femoral artery model of simulated PAD. We hypothesized that in decerebrate, unanesthetized rats, B2-R blockade with 100 ng of the B2-R antagonist HOE-140 would result in a greater attenuation of the pressor and cardioaccelerator response to 30 seconds of 1 Hz dynamic hindlimb skeletal muscle stretch in rats with a femoral artery ligated for ~72 hours compared to rats subjected to a sham procedure in which the femoral artery remained freely perfused. In the ligated condition (n = 14), we found that HOE-140 had no effect on the peak ΔMAP (pre: 37 ± 4, post: 32 ± 5 mmHg, p = 0.14) or peak ΔHR (pre: 15 ± 3, post: 15 ± 2 bpm, p = 0.78) response to stretch. In the freely perfused condition (n = 5), we likewise found that HOE-140 had no effect on the peak ΔMAP (pre: 16 ± 5, post: 16 ± 3 mmHg, p = 0.79) or peak ΔHR (pre: 7 ± 3, post: 8 ± 2 bpm, p = 0.91) response to stretch. Based on these results, we conclude that B2-R signaling in sensory neurons is not required to produce the chronic mechanoreflex sensitization present in the rat model of simulated PAD in which a femoral artery is chronically ligated.
Keywords: Mechanoreflex; Exercise pressor reflex; Peripheral artery disease